2005
DOI: 10.1111/j.1462-2920.2005.00892.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration and resilience of the soil microbial community following compost amendment: effects of compost level and compost‐borne microbial community

Abstract: Compost amendment has been reported to impact soil microbial activities or community composition. However, little information is available on (i) to what extent compost amendment concurrently affects the activity, size and composition of soil microbial community, (ii) the relative effect of the addition of a material rich in organic matter versus addition of compost-borne microorganisms in explaining the effects of amendment and (iii) the resilience of community characteristics. We compared five treatments in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
4
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(113 citation statements)
references
References 40 publications
6
93
4
3
Order By: Relevance
“…Recent studies using molecular techniques have identified detectable changes within Proteobacteria, Acidobacteria and Bacteroidetes with the use of organic amendments [174,175]. Another recent study suggested that compost effects were mainly caused by physicochemical characteristics of the compost matrix rather than by compost-borne microorganisms and that there was no resilience of microbial characteristics during the study (6-12 months) after applying a high amount of compost [176]. However, a comprehensive meta-analysis showed that organic amendments routinely increased soil microbial biomass in agricultural soils [177].…”
Section: A General Approach: Modify the Whole Soil Communitymentioning
confidence: 99%
“…Recent studies using molecular techniques have identified detectable changes within Proteobacteria, Acidobacteria and Bacteroidetes with the use of organic amendments [174,175]. Another recent study suggested that compost effects were mainly caused by physicochemical characteristics of the compost matrix rather than by compost-borne microorganisms and that there was no resilience of microbial characteristics during the study (6-12 months) after applying a high amount of compost [176]. However, a comprehensive meta-analysis showed that organic amendments routinely increased soil microbial biomass in agricultural soils [177].…”
Section: A General Approach: Modify the Whole Soil Communitymentioning
confidence: 99%
“…Compost is a microbiologically active product characterized by a particular endogenous microflora (Saison et al 2006). The techniques of molecular biology offer new opportunities for analyzing changes in soil microbial communities (Dilly et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to accelerate the process of biodegradation, mix thus formed horizons, adding new material, aerating the pile and destroying/orienting/modifying a natural system in formation. With these operations, farmers and gardeners purposely interfere with the natural process of organic matter decomposition and transform natural humus systems into Techno humus systems (Mustin, 1987;Culot and Lebeau, 1999;Tuomela et al, 2000;Ouédraogo et al, 2001;Fontaine et al, 2003;Annabi et al, 2005;Ros et al, 2006;Saison et al, 2006;Evanylo et al, 2008;Adani et al, 2009;Lowenfels and Lewis, 2010;Brown and Cotton, 2011;Zhao et al, 2013;Lowenfels, 2014;Gerbier, 2015;Kuzyakov and Blagodatskaya, 2015;Lowenfels, 2017).…”
Section: Manure Humus Systems: Techno Humus Systems With Soil Createdmentioning
confidence: 99%